High‐performance alternating current electroluminescent layers solution blended with mechanically and electrically robust nonradiating polymers. Issue 23 (6th August 2015) - Jo, Seong Soon; Cho, Sung Hwan; Kim, Hae Jin; Nam, Taewook; Hwang, Ihn; Jung, Seok‐Heon; Kim, Richard Hahnkee; Velusamy, Dhinesh Babu; Lee, Ju Han; Park, Taejoon; Lee, Jin Kyun; Kim, Dae‐Eun; et al.
ABSTRACT Organic and polymeric electroluminescent (EL) devices working under alternating current (AC) electricity have drawn technological attention due to their light‐emitting principles and have great potential for applications. In spite of recent advances in AC EL devices, mechanically robust, patternable full‐color emission layers with high brightness have rarely been demonstrated. In this manuscript, we report high‐performance full‐color AC EL devices with nonradiating polymers solution blended in fluorescent polymer emissive layers. Conventional nonradiating polymers such as poly(styrene) (PS) and poly(α‐methyl styrene) in an emissive layer enhanced the brightness of individual red (R), green (G), and blue (B) colors to several thousand cd m−2. Systematic investigation revealed bi‐functional roles of PS not only as a diluting agent but also as an electron capturer. This resulted in the hole and electron carriers being balanced in the emissive layer, leading to improved power and current efficiency. Furthermore, our blended emission film consisting of 83 vol % PS is mechanically robust with excellent surface adhesion as well as uniformity, when combined with scratch‐tolerant AC device architecture, not only resulted in large area cell operation but also allowed for a solution‐based pattern‐mask process, giving rise to well‐defined R, G, and B cells individually addressable in a single device platform. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2015, 53, 1629–1640